Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Kinerja Guru Studi Pada SMP PGII 1 Kota Bandung - Wiara Sanchia Grafita Ryana Devi (Universitas Insan Cendekia Mandiri, 2019)
Abstract: This study aims to analyze the Effect of Organizational Commitment and Job Satisfaction on Teacher Performance and to find out Organizational Commitment, Job Satisfaction and Teacher Performance in SMP PGII 1 Bandung. Where the population of 43 by using a sampling technique that is saturated sample where the entire population is sampled. The research method used in this research is descriptive research method and multiple correlation analysis data processing assisted with SPSS V 23.0 for Windows. The statistical test results partially show that Organizational Commitment has no significant effect on Teacher Performance. Job Satisfaction has a significant effect on Teacher Performance. Simultaneously the results of the study indicate that there is an influence between Organizational Commitment, and Job Satisfaction significantly influence Teacher Performance.